Effect of formaldehyde inhalation on Hsp70 in seminiferous tubules of rat testes: an immunohistochemical study - Özen, OA; Akpolat, N; Songur, A; Kus, I; Zararsiz, I; Özaçmak, VH; Sarsilmaz, M (Sage Publications Inc, 2005)
One parameter which might provide an insight into the underlying mechanism of the effect of formaldehyde (FA) inhalation on testicular tissue, is the assessment of heat shock protein 70 (Hsp70), which increases promptly in cells exposed to stress caused by chemical toxicity. Thus, following subchronic exposure at cytotoxic concentrations, we studied the immunohistochemical effect of FA inhalation on changes in Hsp70 content in testicular tissue. We used 18 albino Wistar rats divided into three groups, exposed to 0 (control), 5 and 10 ppm FA gas for a total of 91 days, 8 h/day, five days a week. Serum testosterone levels were determined using a chemiluminescent enzyme immunoassay. Testicular tissues were stained with Hematoxylin-Eosine and Hsp70 immunohistochemically performed. Diameters of seminiferous tubules and serum testosterone levels in animals inhaling FA were significantly decreased. In seminiferous epithelium stained for Hsp70, compared to those in the control group, the spermatogenetic cells in the experimental groups demonstrated an obvious increase in immunoreaction spermatides in the adluminal region and especially in the cytoplasm of spermatocytes. Immunoreaction of Hsp70 was detected in the spermatogonias of animals exposed to FA inhalation as opposed to those of the control group. Compared to the control, there was a significant increase in the immunoreactions observed not only in the cytoplasm of primary spermatocytes, but also spermatides in the adluminal region of the seminiferous tubules. In conclusion, FA gas may damage spermatogenetic cells and increase Hsp70 synthesis.
Keywords: formaldehyde exposure; Hsp70; inhalation; seminiferous tubule; testis